AN ESSAY ON TERRITORIAL DEVELOPMENT: FROM THE ENCOURAGEMENT OF ENTREPRENEURSHIP IN EUROPE TO THE FIGHT AGAINST POVERTY IN LATIN AMERICA - Freitas Coca, Estevan Leopoldo de [UNESP]; Barbosa Junior, Ricardo (Univ Federal Roraima, 2016)
Since the early 2000s, multiple territorial development policies have been applied in Latin America as a way to fight poverty and promote economically and socially stagnant regions. In this essay, we highlight how these policies are subsidised by European experiences. With the purpose of proposing a rupture from the dichotomous approach: capitalist strengthening strategy versus emancipatory proposal. To this end, a comprehensive literature and documental review was conducted seeking to understand the dynamics that characterize territorial development in Latin America. Thus, we argue that the incorporation of the territorial approach of development in Latin America is the product of the contradictions of governments, whom although have not structurally ruptured with capitalism, have given space for more socially oriented policies.
Keywords: Latin America; territorial development; social policy; combating poverty; civil society